(untitled) (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
The transformation of digital technology has changed the way students interact and carry out their daily activities, particularly through the increasingly intensive use of smartphones. This usage facilitates communication and access to information, but it also poses the risk of addictive behavior that can reduce focus, productivity, and the overall quality of academic life. This study aims to identify the level of smartphone addiction and its impact on the sleep quality of students at UIN Suska Riau. The research uses a quantitative approach with purposive sampling techniques involving 30 students. The questionnaire used for variable X (smartphone addiction) consists of 10 statement items based on the SAS-SV (Smartphone Addiction Scale – Short Version), while the questionnaire used for variable Y (sleep quality) consists of 10 statement items based on the PSQI (Pittsburgh Sleep Quality Index). The results show that the majority of students have a high pattern of smartphone use leading to addiction, characterized by excessive usage, difficulty in time management, and negative impacts on academic activities. These findings highlight the importance of addressing smartphone addiction in higher education environments